Qualidade na produção de refeições de uma Unidade de Alimentação e Nutrição (UAN) - Silva, Caroline de Barros Gonçalves da [UNESP]; Aranha, Flavia Queiroga [UNESP] (My University, 2011)
This study aimed to evaluate the food production and then act to increase the quality and security of a service, in order to meet the requirements for qualification HAPPC, using good manufacturing procedures as starting point for implementation. It is characterized as an intervention study, emphasizing the quality of foods and the use of good manufacturing procedures at the foodservice and nutrition units, located in Botucatu-SP. It was composed of 2 moments. In the first, we applied a check-list for ascertainment of non-conformity and in the second moment a training “in loco” was given for the collaborators. The lack of hygienic cleaning of hands is seen as an important negative point. We verified that the biggest difficulties and irregularities are related to the manipulators which don´t follow the rules. Good manufacturing procedures were obtained to increase the quality and the security of foods in the unit, but these must be kept constantly adjusted to the standards.

O estudo teve como objetivo avaliar e atuar em uma Unidade de Alimentação e Nutrição (UAN) para aumentar a qualidade e segurança dos alimentos produzidos, a fim de buscar a qualificação da Análise de Perigo e Ponto Crítico de Controle (APPCC), utilizando as Boas Práticas de Fabricação (BPF) como ponto de partida para implementação. Caracteriza-se como um estudo de intervenção, enfatizando a qualidade dos alimentos e a utilização de BPF de uma UAN, localizada em Botucatu, SP. Foi dividido em dois momentos, o primeiro com aplicação de check-list para averiguação das não-conformidades, e o segundo momento um treinamento “in loco” para os colaboradores. A falta de freqüência de higienização das mãos foi vista como um ponto importante e verifica-se que as maiores dificuldades e irregularidades são em relação aos manipuladores que não cumprem as regras. Conseguiu-se aumentar a qualidade e a segurança dos alimentos na unidade, mas estes devem ser mantidos constantemente, para enfim adequar-se ao APPCC.
Quality in the production of meals for foodservice and nutrition units
Keywords: Good manufacture procedures; Nutrition; Food hygiene; Foodservice and nutrition units; Boas práticas de fabricação; Nutrição; Higiene de alimentos; Unidade de alimentação e nutrição